2014
DOI: 10.4314/ahs.v14i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Primary Open Angle Glaucoma Patients in Rural and Urban Ghana

Abstract: Abstract:Purpose: To compare the clinical features of glaucoma patients who present at a rural hospital in North Eastern Ghana and an urban hospital in the capital city of Accra. Methods: This is a multi-center retrospective case series involving records of newly diagnosed glaucoma patients with emphasis on primary open angle glaucoma (POAG). Information collected included basic demographic data, intraocular pressures and optic disc measurements. Results: A total of 949 patients (437 rural; 512 urban; 1868 eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…1,7 Raised intraocular pressure (IOP) is the most principal risk component for POAG advancement and is the paramount therapeutic index. 2 In white populations, the correspondence between IOP and refractive error has been reported. In these studies, myopia and hyperopia were associated with the risk of ocular hypertension, however, myopic eyes were more predisposed to higher IOPs than hyperopic or emmetropic eyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7 Raised intraocular pressure (IOP) is the most principal risk component for POAG advancement and is the paramount therapeutic index. 2 In white populations, the correspondence between IOP and refractive error has been reported. In these studies, myopia and hyperopia were associated with the risk of ocular hypertension, however, myopic eyes were more predisposed to higher IOPs than hyperopic or emmetropic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Primary open angle glaucoma (POAG) is the most typical reported type of glaucoma in population-based prevalence investigations globally; and the most frequent source of irremediable adult blindness in African nations, inflicting a considerable misfortune both on individuals and society. 1,2 The comparative chance of open angle glaucoma has been observed to heighten increasingly as refractive level shifts from hypermetropia to myopia. 3,4 Accordingly, there is a prominent prevalence of glaucoma in myopic eyes than in any other refractive errors or emmetropic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Al Mansouri F (2002) in Qatar found fewer males (41.6%) and more females (58.4%) to be suffering from POAG. 24, [29][30][31][32] In the present study, 40% patients were from rural area and 60% from the urban populace. In the Chennai Glaucoma Study by Lingam Vijaya et al (2008), the prevalence of POAG in a ≥ 40 years old South Indian urban population was 3.51% higher than the rural population.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, our results on the association between residential area and glaucoma surgery rates were different from our expectation. A previous study that compared the characteristics of patients with primary OAG in rural and urban areas reported a higher percentage of uncontrolled IOP and more structural damage in the rural area 20 . The percentage of unilateral and bilateral blindness was also higher in the rural area (52.2%, 34.1% in rural, 32.9%, 17.5% in urban, respectively) compared with the urban area 20 .…”
Section: Discussionmentioning
confidence: 93%
“…A previous study that compared the characteristics of patients with primary OAG in rural and urban areas reported a higher percentage of uncontrolled IOP and more structural damage in the rural area 20 . The percentage of unilateral and bilateral blindness was also higher in the rural area (52.2%, 34.1% in rural, 32.9%, 17.5% in urban, respectively) compared with the urban area 20 . In contrast to the pervious study, our study reported that metropolitan areas had the highest OR for glaucoma surgery.…”
Section: Discussionmentioning
confidence: 93%